2022
DOI: 10.1051/0004-6361/202244203
|View full text |Cite
|
Sign up to set email alerts
|

Transmission spectroscopy of the ultra-hot Jupiter MASCARA-4 b

Abstract: Context. Ultra-hot Jupiters (UHJs), rendering the hottest planetary atmospheres, offer great opportunities of detailed characterisation with high-resolution spectroscopy. MASCARA-4 b is a recently discovered close-in gas giant belonging to this category. Aims. We aim to characterise MASCARA-4 b, search for chemical species in its atmosphere, and put these in the context of the growing knowledge on the atmospheric properties of UHJs. Methods. In order to refine system and planet parameters, we carried out radia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 110 publications
4
19
0
Order By: Relevance
“…The simulations ran for a total of 2000 plane-tary days. Our GCM assumes hydrostatic equilibrium, which is a valid assumption for the opacity sources included in the high-resolution spectra we calculate from these models (Zhang et al 2022).…”
Section: Gcmmentioning
confidence: 99%
“…The simulations ran for a total of 2000 plane-tary days. Our GCM assumes hydrostatic equilibrium, which is a valid assumption for the opacity sources included in the high-resolution spectra we calculate from these models (Zhang et al 2022).…”
Section: Gcmmentioning
confidence: 99%
“…Day-to-night wind flow in KELT-9b was also reported by Pai and Bello-Arufe et al (2022) based on the Doppler shift of Fe ii lines seen in transmission compared to the stellar systemic velocity. While Fe i traces gas motions in the gravitationally bound part of the atmosphere of a planet, Fe ii is likely tracing the dynamics of the evaporating exosphere (Zhang et al 2022). Therefore, a full analysis combining highspectral-resolution phase curves and transmission spectroscopy of UHJs has the potential to illuminate the physical processes leading to mass loss in this class of exoplanets.…”
Section: Implications For Wind Dynamics Measured In Transmission Spec...mentioning
confidence: 99%
“…3.2.1. Template Spectra Zhang et al (2022) reported excess absorption by Hα, Hβ, Na I D1&D2, and Ca II H&K, and strong lines of Mg, Fe, and Fe+, and detected the species Mg, Ca, Cr, Fe, and Fe+ using the cross-correlation technique. Given its high equilibrium temperature, we suspected that this planet might also bear heavier species, as found in the atmospheres KELT-9 b, WASP-121 b and WASP-76 b (Hoeijmakers et al 2019;Azevedo Silva et al 2022).…”
Section: Survey Of Atoms and Molecules Using The Crosscorrelation Tec...mentioning
confidence: 99%
“…MASCARA-4 b is an UHJ with a mass of 1.675 ± 0.241 M Jup , a radius of 1.515 ± 0.044 R Jup , and an equilibrium temperature T eq of 2250 ± 62 K with an orbital period of ∼2.82406 days (Dorval et al 2020;Zhang et al 2022). Thus, it is an ideal target for atmospheric characterization given its large atmospheric scale heights and TSM (Kempton et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation